Peers’ Income and Financial Distress: Evidence from Lottery Winners and Neighboring Bankruptcies - Agarwal, Sumit; Mikhed, Vyacheslav; Scholnick, Barry (Review of Financial Studies, 2020)
Abstract We examine whether relative income differences among peers can generate financial distress. Using lottery winnings as plausibly exogenous variations in the relative income of peers, we find that the dollar magnitude of a lottery win of one neighbor increases subsequent borrowing and bankruptcies among other neighbors. We also examine which factors may mitigate lenders’ bankruptcy risk in these neighborhoods. We show that bankruptcy filers obtain more secured, but not unsecured, debt, and lenders provide additional credit to low-risk, but not high-risk, debtors. In addition, we find evidence consistent with local lenders taking advantage of soft information to mitigate credit risk. Received October 12, 2016; editorial decision January 15, 2019 by Editor Philip Strahan. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.